Sexual Harassment in Public Medical Schools in Ghana - Norman, I.D.; Aikins, M.; Binka, F.N. (Ghana medical journal, 2013)
Objective: This study investigated the prevalence and incidence of Traditional (where a person in a position of power harasses a subordinate) and contra power sexual harassment, (where a subordinate is the harasser of authority figure) in medical schools in Ghana. among Design: Cross-sectional study Method: Four hundred and nine medical students from four medical schools in Ghana were interviewed. We also considered if academic and financial dependence would predict either traditional or contra power sexual harassment. We further investigated, whether women were more bothered by sexual harassment than men and the correlation between sexual harassment and health. Results: Women were 61% more likely to be sexually harassed than men 39%. Sexual harassment negatively affects the victims’ health outcome. We found that the traditional form of sexual harassment was prevalent in medical schools in Ghana and that academic dependence predicted attacks. In the first and second years, women at these institutions are more likely to be sexually harassed than men. Conclusion: Sexual harassment policies of medical school need to be widely circulated. The various medical schools should provide reporting procedures and counseling for victims. This paper would inform policy and research.
Journal Article
Keywords: Sexual Harassment; Health; Medical Schools; Ghana